Traditional agri-food products as a leverage to motivate tourists: A meta-analysis of tourism-information websites. Issue 2 (19th November 2019) - Cafiero, Carlo; Palladino, Monica; Marcianò, Claudio; Romeo, Giuseppa
Abstract : Purpose: This paper aims to provide evidence on the extent to which traditional agri-food products (TFPs) constitute a leverage to promote tourism in the province of Reggio Calabria, Italy, and discuss ways in which community-led local development governance institutions might enhance it. Design/methodology/approach: The study is based on a review of existing information on Calabrian TFPs to classify them by area of production and identify those that are specific or relatively small areas, in addition to a qualitative analysis of the content of the texts of a sample of websites promoting tourism in the region. Findings: Though food is one of the leverages used to promote tourism in Calabria, TFPs are not yet sufficiently exploited to attract tourists to the province of Reggio Calabria, in spite of their potential as a vital expression of local culture and traditions. Research limitations/implications: The selection of the websites used in the study may not be exhaustive of the full spectrum of Web-based promotion of tourism in Calabria. Practical implications: The results provide useful insights to public and private institutions responsible for rural development and tourism promotion in Calabria. The database on the TFPs of the province of Reggio Calabria permits an easy reading of the geographical distribution of the different categories of products, useful as a resource for further studies and as a local development policy support tool. Social implications: Promoting a form of culturally sensitive, food-based tourism in the interior areas of Calabria may constitute an important factor to revert the trend towards impoverishment, migration of young people and depopulation of the interior areas of Calabria. This is a particularly sensitive issue in Italy today, in view of the difficulties that other strategies pursued in the area are facing. Originality/value: Existing literature on typical food products in Italy focuses on those labelled by denomination of origin and geographic protection. This is one of the first papers focusing on TFPs labelled as Prodotti agroalimentari tradizionali in the Italian legislation. By exploring the role of local food and traditions in promoting tourism, this paper expands the scope of existing studies of rural tourism and on rural development in Calabria, and beyond.